Improvement on Processing Technology of Thin Plate Gears - Wu Qingyu; Yin Yaojun; Yao Suxian; Yang Hongping (Jixie chuandong)
Aiming at the deformation of thin plate gears, the main reasons are analyzed as follows: large residual stress after machining, large thermal stress and structural stress during heat treatment, effects of grinding heat, poor rigidity of parts during grinding, large flatness error of locating surface, unreasonable arrangement of finishing process and unstable clamping. Combined with the actual processing, several improvement measures are put forward, such as optimizing the structure of heat treated parts, reducing the influence of machining residual stress, reducing the flatness error of locating surface, optimizing the finishing process and improving clamping stability. It is verified that these improvement measures have positive impact and ensure the accuracy of parts, which provides technical reference for similar thin plate gear parts.